Advertising at war : business, consumers, and government in the 1940s - Stole, Inger L. (University of Illinois Press, 2012)
'Advertising at War' challenges the notion that advertising disappeared as a political issue in the United States in 1938 with the passage of the Wheeler-Lea Amendment to the Federal Trade Commission Act, the result of more than a decade of campaigning to regulate the advertising industry. Inger L. Stole suggests that the war experience, even more than the legislative battles of the 1930's, defined the role of advertising in U.S. postwar political economy and the nation's cultural firmament.
Keywords: Advertising Council -- History.; Advertising Council; Advertising -- United States -- History -- 20th century.; World War, 1939-1945 -- United States -- Propaganda.; Corporations -- Public relations -- United States -- History -- 20th century.; United States -- History -- 1933-1945.; Guerre mondiale, 1939-1945 -- États-Unis -- Propagande.; Sociétés -- Relations publiques -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Histoire -- 1933-1945.; HISTORY -- Military -- World War II.; LANGUAGE ARTS & DISCIPLINES -- Communication Studies.; Advertising; Corporations -- Public relations; Propaganda; United States; 1900-1999; Electronic book.; History